Non - Invasive hemodynamic parameters as predictors for hypotension following spinal anesthesia in parturients undergoing lower segment cesarean section: A prospective observational study - Neelam Singhal; Amol Bansal; Rashmi Duggal (Wolters Kluwer Medknow Publications, 2023)
Background: In parturients undergoing lower segment cesarean section (LSCS) following spinal anesthesia hypotension is the most common side effect that may cause severe adverse effects in mothers such as nausea, vomiting, and dizziness. Very few studies have been done in the Indian population wherein multiple non-invasive hemodynamic parameters have been studied as predictors of hypotension following spinal anesthesia in parturients undergoing cesarean section. So we hypothesized that multiple non-invasive hemodynamic parameters like Perfusion Index (PI), Pleth Variability Index (PVI), and heart rate (HR) can predict hypotension following spinal anesthesia in parturients undergoing an elective cesarean section. Methods: We enrolled 40 parturients in this prospective observational study. Spinal anesthesia was performed with 10 mg of injection bupivacaine 0.5% (hyperbaric) at the L3-L4 or L2-L3 interspaces. Hypotension in parturient was defined as decrease in systolic blood pressure of greater than 20% from its baseline value. Baseline HR, PVI, and PI were recorded. Statistical analysis was performed using Unpaired t-test/Mann-Whitney test and Chi-Square test/Fisher's exact tests. Area under the receiver operating characteristic (ROC) curve (AUC) was used to determine the sensitivity, specificity, and the cut-off value for the parameters. Results: Hypotension occurred in 57.5% of the parturients. It was observed that only PI could predict the development of post spinal hypotension in parturients undergoing LSCS (AUC = 0.835, 95% confidence interval [CI] 0.684-0.933, P = 0.001). The analysis of ROC curve was done and a new cut-off value of PI of >2.58 was found with 100% sensitivity and 70.6% specificity for predicting post-spinal hypotension, which was highly statistically significant, P value <0.001. Conclusion: The baseline PI is a useful predictor for hypotension in parturients undergoing spinal anesthesia. Other non-invasive hemodynamic parameters, that is baseline HR and PVI, however, could not anticipate hypotension in these parturients.